2013
DOI: 10.1002/nbm.3001
|View full text |Cite
|
Sign up to set email alerts
|

Reliable chemical exchange saturation transfer imaging of human lumbar intervertebral discs using reduced‐field‐of‐view turbo spin echo at 3.0 T

Abstract: The reduced field-of-view (rFOV) turbo-spin-echo (TSE) technique, which effectively suppresses bowel movement artifacts, is developed for the purpose of chemical exchange saturation transfer (CEST) imaging of the intervertebral disc (IVD) in vivo. Attempts to quantify IVD CEST signals in a clinical setting require high reliability and accuracy, which is often compromised in the conventionally used technique. The proposed rFOV TSE CEST method demonstrated significantly superior reproducibility when compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Taken together, the observed loss of gagCEST effect with age may be explained by a loss of glycosaminoglycans due to physiological IVD degeneration and proteolysis in the aging discs. This finding is consistent with data acquired by Haneder et al and Liu et al, which show a decrease of gagCEST effect with anatomical disc degeneration. Our study is limited by a lack of knowledge of the true glycosaminoglycan content, which might be assessed by histological samples only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, the observed loss of gagCEST effect with age may be explained by a loss of glycosaminoglycans due to physiological IVD degeneration and proteolysis in the aging discs. This finding is consistent with data acquired by Haneder et al and Liu et al, which show a decrease of gagCEST effect with anatomical disc degeneration. Our study is limited by a lack of knowledge of the true glycosaminoglycan content, which might be assessed by histological samples only.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we used the same B 1 amplitude averaged over time as reported by Haneder et al However, different field strengths have been used previously for gagCEST imaging (Liu et al: 0.8 μT, Saar et al: 1.8 μT, Kim et al: 1.5 μT in phantoms and 0.75 μT in IVDs) . The B 1 amplitude could have an influence on both, the gagCEST asymmetry as well as the spillover effect.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with T2 mapping, T1ρ imaging possesses a better dynamic range and, hence, a better sensitivity to tissue hydration and PG content change during IVDD . Chemical exchange saturation transfer (CEST) imaging can detect GAG loss, and several studies have demonstrated the feasibility of CEST imaging of GAG content and pH changes during IVDD . The use of 23 Na MRI has also been explored for measuring the sodium concentration in intervertebral disc as an index for fixed charge density and GAG content in the ECM .…”
Section: Introductionmentioning
confidence: 99%
“…A two‐dimension (2D) reduced field‐of‐view (rFOV) TSE CEST sequence was previously introduced . rFOV can effectively suppress motion artifacts caused by bowel movement, and improve measurement reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…Post processing was performed with custom‐written programs in Matlab (The Mathworks, Natick, MA). CEST images were processed as previously described . Spin‐lock images at different SLTs were fitted into a mono‐exponential decay model to obtain R 1ρ values using least‐squares fitting, pixel by pixel.…”
Section: Methodsmentioning
confidence: 99%